Applicability of Active Downdraught Cooling in Hot and Humid Climate in China. (2017) - Xuan, Huang; Lian, Zhiwei; Ford, Brian
Abstract: This study investigates the applicability and performance of Active Downdraught Cooling (ADC) in hot and humid regions of China through a field testing at the Centre for Sustainable Energy Technologies Building (CSET). In an ADC system, buoyancy driven air movement is a key element of success and is the focus of this study. Design elements influencing air movement and the effect of other passive strategies and outside conditions on the systems performance are examined, by the comparison of data collected through a one month period, spot measurements and smoke tests. Measurement data show that indoor temperatures moved around 22 ºC while outdoor temperatures reached over 34-35ºC, proving that ADC is a viable alternative to air-conditioning. However, problems such as opposite air movement and technical faults were observed and influenced the system's performance. Proposals are given on how to eliminate problems and on how to improve the system's performance further.